MEG/EEG Group Analysis With Brainstorm - Tadel, François; Bock, Elizabeth; Niso, Guiomar; Mosher, John C.; Cousineau, Martin; Pantazis, Dimitrios; Leahy, Richard M.; Baillet, Sylvain (Frontiers in Neuroscience, 2019)
(MEG), (EEG), Brain Imaging Data Structure (BIDS), Open data, Group analysis, Good practice, Reproducibility, Open source.